Decision support for parenteral nutrition supplementation in ICU using model-based glycemic control protocol - Abu-Samah, Asma; Abdul Razak, Normy Norfiza; Mohamad Suhaimi, Fatanah; Jamaludin, Ummu Kulthum; Md Ralib, Azrina; Mat Nor, Mohd Basri; Chase, Geoffrey (Springer Verlag, 2018)
Nutrition therapy is part of the standard care given to all critically ill patients. In general, nutrition is administered as enteral nutrition (EN) and/or parenteral nutrition (PN). PN is given if the patients have contraindications to EN or as supplement if daily energy requirement cannot be achieved by EN alone. PN can be given as partial (dextrose solution only) or complete (include all macro- and micro-nutrients). The mode of nutrition therapy is influenced by several factors which include the need to maintain normoglycemia. A simulation is done to find the appropriate time to introduce PN while the patients are already on EN. In this context, a virtual study was conducted on 66 retrospectives critically ill patients’ data using clinically validated insulin-nutrition model and Stochastic TARgeted (STAR) protocol. The results suggested that this protocol benefited critically ill patients in two-fold. This approach is not only useful in controlling per-patient normoglycemic level, but also able to recognize the time for PN supplement when patients become hypoglycemic. This serves as a potential decision support in the intensive care environment when healthcare providers faced with the complexity of dynamics between good glycemic control and optimized nutrition therapy.